The The Moderating Role of Work Engagement in the Relationship between Workplace Spirituality and Innovative Work Behavior Among General Practitioners: A Meta-Analysis - Umi Kulsum; Djazuly Chalidyanto (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to examine the moderating role of work engagement in the relationship between workplace spirituality (WS) and innovative work behavior (IWB) among general practitioners (GPs). A systematic review and meta-analysis were conducted following PRISMA (2021) guidelines. A comprehensive search across Scopus, Web of Science, PubMed, ProQuest, ScienceDirect, and Google Scholar identified 16,800 records. After removing duplicates (n = 3,215) and screening, seven quantitative studies (N = 3,025 GPs) were included. A random-effects model was applied due to substantial heterogeneity (I² = 91.35%). The results showed a moderate and significant positive relationship between WS and IWB (r = 0.52, 95% CI [0.42–0.60]). A narrative comparison based on study characteristics suggested that work engagement may strengthen this relationship, with stronger associations observed in studies reporting higher employee engagement (r = 0.61) compared to those with lower engagement (r = 0.38). However, formal moderator analysis was limited due to the small number of included studies (k = 7).  Subgroup analysis indicated no significant effect of GP workforce characteristics (p > 0.05). These findings suggest that workplace spirituality enhances innovative behavior through meaning and value alignment, but its effectiveness depends on work engagement. Strengthening both factors may improve physician innovation and support sustainable general practitioners (GPs) aligned with SDG 3.